ANALISIS DAMPAK PERDAGANGAN BEBAS ASEAN TERHADAP PENGEMBANGAN KOMODITAS PANGAN UTAMA INDONESIA - , Saktyanu Kristyantoadi Dermoredjo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Any countryâs involvement in the multilateral or regional blocks has its own interest. Indonesia also has certain interest in ASEAN collaboration such as commodity protection, especially its agricultural commodities either through WTO or ASEAN. In this contending world, the main issue is how to protect domestic production in coping with more competitive worldâs production, especially in dealing with AFTA which will be implemented in 2015. the research objectives are: (1) Analyzing main food supply (rice, corn, and soybean) in terms of food production, agricultural economy, total population, and agricultural value added on GDP, (2) Analysis AFTAâs impacts on enhancement of economy, main food production (rice, corn, and soybean), and demand for production inputs: land, labor, capital, and other natural resources, (3) Analyzing changes in land, production and yields of main food in rural areas, and (4) Analyzing policy priorities on food (rice, corn, and soybean), post harvest, trade, distribution, and consumption. The four objectives are conducted with the tools analysis: Principal Component Analysis (PCA), Global Trade Analysis Project (GTAP) Model, Descriptive Analysis and Analysis Hierarchy Process (AHP). Rice, maize and soybean stock are not parallel with its production growth. This decrease could be due to increased planting of corn and rice crops, causing soybean decreased. Along with increase of land holding area, the production also increases but it does not correspond to yield improvement, but in the period 2006-2010 the production has decreased in all regions. In terms of free trade impacts, all policies are directed toward communityâs welfare. It is, however, is not suggested for corn and soybean in Java and other objectives are various. Output drop of rice commodity in Indonesia due to lower tariff in ASEAN countries indicates that Indonesia still needs more comprehensive policy on product development. In addition, various policies are required in developing rice, corn, and soybean both in Java and outside Java.